Sociodemographic profile of family caregivers of elderly people with Parkinson's Disease: prerequisite for the construction of a unique instructional guide (Research, Society and Development, 2022)
The population growth of aging presents great biopsychosocial and economic concerns, in detriment of the existing expenses in public health. Among these concerns, the Non Progressive Chronic Diseases (NCD) stand out for presenting disabilities, in its overwhelming majority, of the elderly, which brings a family member in the act of caring, in helping or even in the execution of personal and daily activities of the elderly. Parkinson's disease (PD) is the second NCD that transforms the quality of life of the elderly, requiring specific care, which in turn requires a caregiver who undergoes an unscheduled transition. Objective: To describe the socio-demographic profile of the caregiver-family of elderly people with Parkinson's disease as a requirement for the construction of an instructional guide. Method: 22 elderly people with PD were selected, from April to May 2022, at an elderly rehabilitation center in the state of Pará, in the search to analyze only 11 (50%) caregiver-family members. The study was of qualitative, applied, exploratory and technical-scientific approach. It is an exploratory, descriptive, and cross-sectional study. Results: In the semi-structured interview of the 11 caregiver-family members, in their various profiles, attention to the caregiver-family members of the elderly with PD was noted and structured planning in the rehabilitation center was necessary. Conclusion: The results suggest that the multiprofessional team needs to know the caregiver in his risk factors to his own health, making this information the basis for an instructional guide.